Menus for movieland : newspapers and the emergence of American film culture - Abel, Richard, 1941- (University of California Press, 2015)
"At the turn of the last century, the main function of a newspaper was to offer 'menus' by which readers could make sense of modern life and imagine how to order their own daily lives. Among those menus in the mid-1910s were several that mediated the interests of movie manufacturers, distributors, exhibitors, and the rapidly expanding audience of fans. This writing about the movies arguably played a crucial role in the emergence of American popular film culture. Negotiating among national, regional, and local interests, it shaped fans' ephemeral experience of moviegoing, their repeated encounters with the fantasy worlds of 'movie land, ' and their attractions to certain stories and stars. Moreover, in weekend pages and daily columns and film reviews, much of this was served up by women and consumed by women, including at least one teenager compiling a rare surviving scrapbook"--Provided by publisher.